PENERAPAN KONSELING BEHAVIORISTIK TEKNIK SELF MANAGEMENT DALAM MENGATASI MALAS BELAJAR SISWA SMA N 1 MEJOBO KUDUS - Lestari, Tia; Santoso, Santoso; Kusmanto, Agung Slamet (Universitas Muria Kudus, 2024)
The objectives of this study are: 1. Knowing the factors that cause students to be lazy to learn, 2. Knowing the extent to which the Behavioristic Counseling approach with Self Management techniques can overcome lazy learning students. The type of research used is a case study. The subjects studied were students of SMA N 1 Mejobo Kudus, there were 2 students who had problems in overcoming lazy learning. Furthermore, the methods used in this study used observation, interviews, and documentation. While the data analysis used is qualitative descriptive data analysis. The results of the study prove that the application of self-management technique behavioristic counseling in overcoming lazy learning in class X-2 students at SMA N 1 Mejobo Kudus can change maladaptive behavior to become adaptive.